The m.7510T > C mutation: Hearing impairment and a complex neurologic phenotype - Laura Kytövuori; Maria Gardberg; Kari Majamaa; Mika H. Martikainen (WILEY, 2022)
Objectives: Mutations in mitochondrial DNA cause a variety of clinical phenotypes ranging from a mild hearing impairment (HI) to severe encephalomyopathy. The MT-TS1 gene is a hotspot for mutations causing HI. The m.7510T>C mutation in MT-TS1 has been previously associated with non-syndromic HI in four families from different ethnic backgrounds.
Materials and Methods: We describe the clinical, genetic, and histopathological findings in a Finnish family with the heteroplasmic m.7510T>C mutation in mitochondrial DNA.ResultsThe family proband presented with a progressive mitochondrial disease phenotype including migraine, epilepsy, mild ataxia, and cognitive impairment in addition to HI. One young adult presented with HI only. Other family members had a mild phenotype comprising ataxia and tremor in addition to HI. Mutation heteroplasmy was 90% in the blood of maternal grandmother and 99% in the muscle and blood of the three other family members. Muscle histology was consistent with mitochondrial myopathy in three family members. The mitochondrial haplogroup of the family was a different branch of the haplogroup H than in the previous reports of this mutation.
Conclusion: Our results suggest that, in addition to sensorineural HI, the m.7510T>C mutation is associated with a spectrum of mitochondrial disease clinical features including migraine, epilepsy, cognitive impairment, ataxia, and tremor, and with evidence of mitochondrial myopathy.